How sponsorship transparency mitigates negative effects of advertising recognition. Issue 3 (3rd April 2019) - Evans, Nathaniel J.; Wojdynski, Bartosz W.; Grubbs Hoy, Mariea
Abstract: The proliferation of covert online advertising formats such as advergames has raised concerns about consumers' ability to recognize such content as advertising and about how recognition affects evaluative outcomes. The present research utilized an online experiment ( N = 179) to examine differences between covertness of advertising format (advergame vs. online video commercials) on advertising recognition, and whether sponsorship transparency mediates – and mitigates – the negative effects of advertising recognition on attitude toward the ad, attitude toward the brand, and purchase intent. The results show that covertness of advertising format, recognition, and sponsorship transparency all shape consumers' responses to online ads. Specifically, the predicted negative indirect effect of covertness of advertising format on attitudes and behavioral intention via advertising recognition reversed valance when sponsorship transparency was included in the serial mediation model.